Silence and Eye Contact: Unveiling Non-Verbal Cues in Passive Language Learners - Rahman, Ali Wira; Dollah, Syarifuddin; Sakkir, Geminastiti (ELT Worldwide: Journal of English Language Teaching, 2025)
Non-verbal cues like eye contact and silence are crucial for classroom engagement, especially for passive students in English language learning environments. Nonetheless, these actions are frequently misunderstood, with eye contact taken as a sign of understanding and silence viewed as a lack of interest or uncertainty. This investigation examines the ways in which passive students utilize eye contact and silence as markers of engagement and comprehension, with the goal of offering a detailed insight into these non-verbal cues during classroom interactions. A descriptive qualitative approach was employed to observe six purposively selected passive students through the use of questionnaires and semi-structured interviews. Thematic Analysis was employed to analyse the data, facilitating the identification of patterns in students' non-verbal behaviours. The results indicate that eye contact from passive students frequently functions as a courteous gesture instead of an indication of comprehension, whereas silence embodies a range of motivations, such as cultural conventions, introspection, and evasion of social pressure. This study emphasizes the importance of educators embracing a contextual approach when interpreting non-verbal cues, thereby fostering a more inclusive learning environment that recognizes various communication styles.